The impact of an education on a healthy nutrition - Jiménez Arrunátegui, Yadira Rosa (2020)
COVID-19 has changed our lifestyle. The words “social distancing” had impacted in celebrations, meetings, reunions, walking and thus, our joy of eating together… and then, with the hope of the reunion. The old guidelines regarding individual health care returned to be used and state of uncertainty covered our lives. The experts have covered the newscasts with science information of the possibly causes and consequences of COVID 19, and some no experts shared advices about an endless number of products and strange mixes about what is good to avoid getting sick or reducing the death risk. The remarkable of all this information is that the word “food” appear frequently. People who don’t have a good food are more susceptible to get sick. On the other hand; people who have good habits food are less vulnerable. To get healthy behaviors take part in the education which it is given both in home as from the educational institutions or educational actions in the Health Promotion. The context of the possibilities of the Nutritional Food Education in Peru is analyzed in the present article.